Kebijakan Luar Negeri Indonesia Terhadap Dukungan Republik Vanuatu Atas Kemerdekaan Papua Barat Tahun 2015-2016 - Bimbi Rianda; Yuswari Octonain Djemat; Angga Nurdin Rahmat (Universitas Jenderal Ahmad Yani, 2017)
Foreign policy stated by Indonesia related to the Republic ofVanuatu support for the Indenpendence of West Papua does not happennaturally. It is influenced by the facts and values that are had by theIndonesia that led to the perception and influences the decision ofmaking process. Indonesia stated that West Papua is a part of therepublic of Indonesia. Therefore, Indonesia states a foreign policy ofRepublic of Vanuatu regarding the support for the independence ofWest Papua. The result of this research indicates that there are someforeign policies of Indonesia against the Republic Vanuatu support forthe Independence of West Papua based on set of orientation, set ofcommitments and a group of behavior action. This research usesrealism approach, the concept of international politics, the concept offoreign policy, the concept of power, the concept of national interest, andthe concept of sovereignty that can explain the foreign policy ofIndonesia against the Republic Vanuatu support for the independenceof West Papua 2015-2016